Economic and evolutionary hypotheses for cross-population variation in parochialism - Hruschka, Daniel J.; Henrich, Joseph (Frontiers in Human Neuroscience, 2013)
Human populations differ reliably in the degree to which people favor family, friends and community members over strangers and outsiders. In the last decade, researchers have begun to propose several economic and evolutionary hypotheses for these cross-population differences in parochialism. In this paper, we outline major current theories and review recent attempts to test them. We also discuss the key methodological challenges in assessing these diverse economic and evolutionary theories for cross-population differences in parochialism.